The effects of croscarmellose sodium concentration on the physicochemical characteristics of orodispersible tablets of atenolol - Parfati, Nani; Rani, Karina Citra (Universitas Ahmad Dahlan, 2018)
Hypertension is the most common cardiovascular diseases suffered by geriatric patients. Their physiological changes make the administration of conventional tablets less effective, especially regarding compliance. One approach to overcome this problem is the development of orodispersible tablets, which soften easily and disintegrate quickly in the oral cavity. Atenolol is a class of Î²-blocker functioning as an anti-hypertensive drug that has been extensively used in hypertension therapy, and it has the potential to being developed as orodispersible tablets. A faster disintegration of orodispersible tablets will facilitate an earlier onset of dissolution. The addition of superdisintegrants can reduce the disintegration time of these tablets. Croscarmellose sodium is a superdisintegrant that can decrease the disintegration time to less than three minutes. This study aimed to optimize the formula of orodispersible tablets of atenolol using different concentrations of croscarmellose sodium, namely 10% (formula 1) and 20% (formula 2). The physicochemical characteristics of the tablets were evaluated to determine the best formula. The evaluation included a comparison to the control formula (0% of croscarmellose sodium). The results showed that formula 1 (10% of croscarmellose sodium) produced orodispersible tablets with the best physicochemical characteristics regarding tablet hardness, friability, in vitro dispersion time, and disintegration time. Formula 1 (%Q30 minutes= 98.31%) also met the standard of the dissolution of atenolol tablets set by the Farmakope Indonesia, i.e., the percent of dissolved drug in 30 minutes has to be higher than 85%. The drug dissolution efficiency of formula 1 was twice higher than that of the control formula.